IMAGOLOGY – A TOOL FOR CREATING THE OTHER IN ELECTRONIC COMMUNICATION. - Grzelak, Eliza (Porównania, 2018)
The author focuses on basic rules of communication, which organize the relationship between the sender and the recipient. She notices that, according to these rules, the responsibility for a correct relationship between the majority group and minority groups, rests on both of them. One of the tasks for the minority groups is effective self-creation which should encourage to learn, improve knowledge and neutralize negative stereotypes. It should also equip the recipient with tools that promote a particular group in both worlds – the real and the virtual. The considerations made by the author are theoretical in nature, but are supported by observations concerning the practical implementation of the presuppositions. The author verifes the theory saying that well-implemented assumptions of imagology can help build the positive image of the minority groups in Poland.